Infected Seymour-Type Fracture: Fratura Seymour-Type Infetada - Branco, Pedro Martins; Baptista, Carolina; Dias, Carlos Maia; Martinho, Gonçalo; Oliveira, Manuel; Silva, António Júlio (Gazeta Médica, 2018)
Extra-articular, transverse, distal phalangeal fractures that involve the physis, are termed Seymour fractures. They are frequently associated with an avulsion of the nail and a laceration of the nail bed. For this type of fractures, sur-gical intervention is needed to explore the fracture site for soft tissue interposition. Its failure may result in several complications. The authors report an adult Seymour-type fracture, which developed an infection due to interposition of the germinal matrix of the nail complex on the fracture site. The purposes of this article are to demonstrate that this rare fracture can also occur in adults, highlight the importance of treating this injury with the basic principles of open fracture treatment, and evidence one of its complications if not well treated.